3D superimposition of craniofacial imaging—The utility of multicentre collaborations. (10th May 2019) - Yatabe, Marilia; Prieto, Juan Carlos; Styner, Martin; Zhu, Hongtu; Ruellas, Antonio Carlos; Paniagua, Beatriz; Budin, Francois; Benavides, Erika; Shoukri, Brandon; Michoud, Loic; Ribera, Nina; Cevidanes, Lucia
Structured Abstract: Clinical applications of 3D image registration and superimposition have contributed to better understanding growth changes and clinical outcomes. The use of 3D dental and craniofacial imaging in dentistry requires validate image analysis methods for improved diagnosis, treatment planning, navigation and assessment of treatment response. Volumetric 3D images, such as cone‐beam computed tomography, can now be superimposed by voxels, surfaces or landmarks. Regardless of the image modality or the software tools, the concepts of regions or points of reference affect all quantitative of qualitative assessments. This study reviews current state of the art in 3D image analysis including 3D superimpositions relative to the cranial base and different regional superimpositions, the development of open source and commercial tools for 3D analysis, how this technology has increased clinical research collaborations from centres all around the globe, some insight on how to incorporate artificial intelligence for big data analysis and progress towards personalized orthodontics.